Dependence of the noise of an orthogonal fluxgate on the composition of its amorphous wire-core - M. Butta (AIP Advances, 2020)
In this paper we study the effect of magnetostriction of Co-rich amorphous microwire to the noise of the orthogonal fluxgates based on such wires. The magnetostriction was modified by changing the relative amount of iron x with the respect of the total amount of cobalt and iron in the alloy. Specifically we changed x in the composition (Co1−xFex)75Si15B10 casting wires with the following values of x: 0.05, 0.055, 0.06, 0.062, 0.065, 0.07 and 0.08. We found out that the noise indeed depends on the composition of the wire: while it is minimum (2.5 pT/Hz) for x between 0.06 and 0.062 where the magnetostriction is vanishing (λs ≈ 10−7) it significantly increases to tens of pT/Hz for both positive and negative magnetostriction when λs becomes one order of magnitude bigger. We verified that once the composition returns a magnetostriction low enough (around x = 0.06) then the noise does not depend on mechanical stress anymore. In fact the noise of a sensor with x = 0.06 is the identical in its natural curved state and when bended straight; for vanishing magnetostriction the bending does not affect at all the noise, as on the contrary it happens with larger magnetostriction. This suggests that once the wire has composition with x = 0.06 the remaining noise is not caused by mechanical stress. Finally we show how to overcome the problem of offset arising after annealing if continuous annealing current is used. We explain how this could be due by the fact that magnetostriction changes with temperature and even a wire with vanishing magnetostriction at room temperature can became significantly magnetostrictive at annealing temperature. For this reason we propose a method of annealing consisting rising the temperature of the wire while the wire is kept in its natural curved state. In this way no mechanical stress is applied to the wire during the annealing process, when the temperature is high enough to make it magnetostrictive even if it is non-magnetostrictive at room temperature. We show how this method suppresses the offset and significantly reduces the noise.